(untitled) (Journal of Geography and Environmental Management, 2019)
The article analyzes the features of the theory of complexity for the dynamics of geographical (territorial) systems from the perspective of the complexity of structures and relations of geosystems of different hierarchical levels. The features of network relationships between the natural and social subsystems of territories are investigated and the role of material and energy flows as system-forming factors of natural-social geosystems is emphasized. The relationship between the level of human communities’ development and the consumption of natural material and energy resources is shown. The analysis of the level of consumption of natural resources in primitive, agrarian and industrial societies showed an increase in anthropogenic consumption of resources critical for natural systems in the industrial era. The article focuses on indicators of material and energy consumption, CO2 emissions between developed and developing countries. The relationship between the standard of living of the population and the consumption of resources is revealed, and the destabilizing role of the West in the global geosystem is also considered. Substantiated methods and approaches are proposed when developing a strategy for the ecological transformation of geosystems, the co-evolution of natural and social structures in them based on the integrated implementation of green economy strategies, post-growth, social and environmental innovations.